EPIGLOTITIS - Elfahmi Elfahmi (Yayasan Nusantara Hasana Berdikari, 2026)
Epiglottitis is an acute and potentially life-threatening inflammation of the epiglottis and surrounding supraglottic structures that can lead to rapid airway obstruction. The condition is commonly caused by bacterial infection, particularly Haemophilus influenzae type b, although viral and fungal infections may also contribute. Epiglottitis can occur in both children and adults, with clinical manifestations including high fever, severe sore throat, dysphagia, drooling, muffled voice, stridor, and respiratory distress. Diagnosis is established through clinical evaluation supported by laryngoscopic examination and radiologic findings, while careful airway assessment remains the primary priority. Prompt management is essential and includes airway stabilization, oxygen therapy, intravenous antibiotics, corticosteroids, and supportive care. Early recognition and rapid intervention are crucial to prevent complications such as complete airway obstruction and respiratory failure.